Management Accounting and Risk Management that Affect the Organizational Effectiveness of Modern Trade in the Digital Age Case Study: Small and Medium-sized Enterprises in Bangkok (SMEs Business) - Pengjinda, Sunun; Songbhanphot, Wasurat; Soontornnon, Watcharee (Rajapark Journal, 2024)
The purpose of this study was to investigate (1) opinions on management accounting, risk management, and organizational effectiveness of medium- and small-sized enterprises in Bangkok. (2) Compare the organizational effectiveness of medium- and small-sized enterprises in Bangkok, categorized by business characteristics. (3) Accounting management and risk management factors influencing the organizational effectiveness of medium- and small-sized enterprises in Bangkok. The study is investigated through a quantitative research approach. The population comprises managers, entrepreneurs, or individuals associated with medium- and small-sized enterprises in Bangkok. A stratified random sampling method with a sample size of 400 is employed. Data is collected using a questionnaire, and statistical analyses involve descriptive statistics such as frequency, percentage, mean, and standard deviation. Inferential statistics include the t-test, one-way ANOVA, least significant difference test (LSD), and multiple regression analysis. The results showed that (1) opinions on management accounting, risk management, and organizational effectiveness of medium- and small-sized enterprises in Bangkok are at a high level. (2) Medium- and small-sized enterprises in Bangkok, different business types exhibit similar organizational effectiveness, except for variations related to business format, operational duration, and total number of employees, which result in distinct organizational outcomes. (3) Accounting management factors about decision-making, directing, and planning, along with risk management factors including operational performance, information management, communication and reporting, strategic planning, objective setting, corporate governance, and organizational culture, significantly influence the organizational performance of medium- and small-sized enterprises in Bangkok, with statistical significance at the 0.05 level.